Exploring feasibility of microwave hyperthermia for pediatric brain tumors - Sykkö, Isabella; Nguyen, Anna (My University, 2024)
Abstract Brain tumors are one of the most common types of childhood cancer [1]. Microwave hyperthermia as an adjuvant treatment has the potential to improve the quality of life and survival rate of patients [2]. Hyperthermia treatment involves heating the target to 40 − 44 ◦C using an antenna array. By tuning the antenna amplitude and phase, positive wave interference in the target increases tumor temperature without damaging healthy tissue. This thesis investigates the feasibility of external microwave hyperthermia for pediatric intracranial tumors. A literature review was done to investigate what tumor sizes and locations are accessible for microwave heating. Craniopharyngioma (≈ 22 ml), diffuse midline glioma (H2K27M) (≈ 31 ml), ependymoma (≈ 49 ml), and meningioma (≈ 55 ml) were identified. Simulations were performed for two study cases to investigate the final temperature distribution and the optimal operating frequency. Specific absorption rate (SAR) based treatment planning and thermal simulations were performed for frequencies between 250 − 800 MHz with self-grounded bow-tie (SGBT) antennas. Case one investigated target size, shape, location, and tissue properties using an 11-year-old patient and a 12-channel array. The chosen tumors, a smaller ependymoma (≈ 7 ml), and a skull base tumor (≈ 11 ml) were tested using four different tissues: (i) healthy, (ii) average of healthy, (iii) tumor (benchmark) [3], (iv) tumor (Schooneveldt) [4]. Case two investigated the effect of different antenna arrangements within an applicator by using a 13-year-old patient with medulloblastoma (126 ml, tumor (benchmark) tissue) and both a symmetric and an optimized 10-channel array. Superficial targets, the ependymoma and meningioma, were the only ones to reach a therapeutically relevant temperature increase. Frequencies between 250 − 350 MHz and frequency combination using 250 − 550 MHz achieved the highest temperature exceeded by 90 % of the target volume, T90, in all targets for both cases. Higher T90 was generally obtained for superficial tumors and for tissues with lower perfusion. A continuation of the thesis would be to investigate optimized arrays at 250 − 350 MHz.
Keywords: Keywords: microwave hyperthermia, pediatric brain tumors, hyperthermia, frequency